Peak to average power ratio reduction based on optimum phase sequence in orthogonal frequency division multiplexing systems - Mohammady, Somayeh (2012)
Orthogonal Frequency Division Multiplexing (OFDM) is a form of a Frequency Division Multiplexing (FDM) scheme that is used in recent broadband wireless communication systems. The main advantage of OFDM systems is immunity against the fading phenomena caused by natural multipath environment. However, there is a major drawback of high Peak-to-Average Power Ratio (PAPR). Signal with high PAPR forces the Power Amplifier (PA) to work in its nonlinear region, which generates distortions. The PA has to be operated with back-off to avoid high PAPR, which decreases the power efficiency. To overcome the PAPR problem in OFDM systems, several techniques are introduced such as Conventional Selected Mapping (C-SLM) and Dummy Sequence Insertion (DSI). In C-SLM method, by increasing the number of Inverse Fast Fourier Transform (IFFT) blocks, the PAPR performance is enhanced at the expense of complexity and side information, which results in high cost and spectrum efficiency degradation. In DSI method, inserting the dummy signals degrades the spectrum efficiency and also exhibits data rate loss. In this thesis, two schemes have been proposed in order to reduce PAPR. The first proposed scheme is called DSI-SLM, which combines the modified dummy sequence of the DSI with the phase sequence of the SLM. As a result of applying this scheme, the PAPR performance is enhanced and the complexity is reduced compared to C-SLM. The second proposed method is named Optimum Phase Sequence with Dummy Sequence Insertion (OPS-DSI) that is designed to improve the DSI-SLM method in terms of complexity and side information. In OPS-DSI method, the optimum phase sequence is applied while only one IFFT is performed and the side information can be placed within the dummy signals. In order to demonstrate the feasibility of these methods in actual systems, the prototype of DSI-SLM and OPS-DSI methods are carried out in Field Programmable Gate Array (FPGA). The implementation results are comparable with simulation results. However,there is less than 0.1dB difference which is due to the constraints of the FPGA input and output bit resolutions. Finally, these methods are integrated with Digital Predistortion (DPD) and actual PA to represent an OFDM transmitter system. This results in Power Added Efficiency (PAE) enhancement by an average of 17%, which leads to less power consumption and prolonged battery life. This system is simulated based on IEEE 802.16e standard and the results are numerically analyzed and compared with various numbers of dummy signals and candidate signals. The DSI-SLM method reduces PAPR by 3.6dB. Almost 76% reduction in total complexity is also achieved compared to CSLM,meanwhile OPS-DSI method enhances PAPR performance by 4.2dB and total complexity reduction by 95%. Hence, OPS-DSI outperforms DSI-SLM in terms of PAPR and complexity. Their Bit Error Rates (BERs) are in acceptable range of 10-4 at Sb/Nb=14 dB.